Corporate Governance, Capital Intensity, dan Tax Avoidance : Bukti Empiris pada Perusahaan Sektor Energi - Diandra Rosiana Latifah; Kinanthi Putri Ardiami (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
This study aims to examine the effect of independent commissioners, audit committees, institutional ownership, managerial ownership, and capital intensity on tax avoidance. The data used in this study consist of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. The sample was selected using a purposive sampling method, resulting in 22 companies or 132 firm-year observations. The data were analyzed using panel data regression analysis, and EViews 12 software was employed to process the data. The results indicate that independent commissioners and audit committees have no significant effect on tax avoidance. Meanwhile, institutional ownership, managerial ownership, and capital intensity have a negative effect on tax avoidance.